Mechanoregulation of clathrin-mediated endocytosis - Ferguson, Joshua P.; Huber, Scott D.; Willy, Nathan M.; Aygun, Esra; Goker, Sevde; Atabey, Tugba; Kural, Comert (COMPANY OF BIOLOGISTS LTD, 2017)
We characterized the tension response of clathrin-mediated endocytosis by using various cell manipulation methodologies. Elevated tension in a cell hinders clathrin-mediated endocytosis through inhibition of de novo coat initiation, elongation of clathrin coat lifetimes and reduction of high-magnitude growth rates. Actin machinery supplies an inward pulling force necessary for internalization of clathrin coats under high tension. These findings suggest that the physical cues cells receive from their microenvironment are major determinants of clathrin-mediated endocytic activity.
Keywords: Clathrin-mediated endocytosis; Membrane tension; Microaspiration; Hypotonic shock; Actin dynamics; CELL POLARITY; LEADING-EDGE; DYNAMICS; CYTOSKELETON; INCREASES; SHAPE; DISC; Cell Biology